1976
DOI: 10.1136/jmg.13.4.295
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome survey of total population of mentally subnormal in North-East of Scotland.

Abstract: The origin of the register for the mentally subnormal has already been described (Innes, Kidd, and Ross, 1968) and in the present paper we report on the results of a cytogenetic survey of these individuals. The survey formed part of a comprehensive study on biochemical, social, psychological, and family aspects of the registered individuals. These other results will be presented elsewhere. 295All persons on the register were included, whether they resided at home or in subnormality hospitals or other instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
1
3

Year Published

1982
1982
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 38 publications
(28 reference statements)
5
28
1
3
Order By: Relevance
“…This figure is close to that in Kuwait (96.2%) (AlAwadi et al, 1990) and it is a little higher than the frequency reported in other countries: Scotland (94.1%) (Speed et al, 1976), UK and Wales (94.3%) (Mutton et al, 1996), and France (94.1%) (Stoll et al, 1990). However, there is a big difference for Belgium (92.1%) Cassiman et al, 1975) and Canada (86%) (Platt et al, 2004).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This figure is close to that in Kuwait (96.2%) (AlAwadi et al, 1990) and it is a little higher than the frequency reported in other countries: Scotland (94.1%) (Speed et al, 1976), UK and Wales (94.3%) (Mutton et al, 1996), and France (94.1%) (Stoll et al, 1990). However, there is a big difference for Belgium (92.1%) Cassiman et al, 1975) and Canada (86%) (Platt et al, 2004).…”
Section: Discussionsupporting
confidence: 85%
“…Other studies reported that the frequency of DS mosaicism varies from 0 to 4.6% (Speed et al, 1976;Monni et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Various surveys have been carried out in the past two decades in different parts of the world to karyotype patients with mental retardation (Sutherland and Wiener, 1971;Cassiman et aL, 1975;Coco and Penchaszadeh, 1976;Speed et aL, 1976;Sutherland et al, 1976;Jacobs et aL, 1978;Moghe et aL, 1981;Wuu et al, 1984). Some researchers have examined the chromosomes of all mental retardates in an institution (Jacobs et aL, 1978) or in a regional population (Speed et aL, 1976), while others have selected the patients before karyotyping (Coco and Penchaszadeh, 1976;Moghe et aL, 1981). These studies unequivocally demonstrate that mentally retarded patients with associated congenital abnormalities have a higher frequency of chromosomal abnormalities than those without.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of chromosome anomalies in mentally retarded males in earlier studies before the fragile-X syndrome was recognized ranged from 11·9% (Speed et al 1976) to 17·6% (Sutherland et al 1976). Institutional screening of mentally retarded males for the fragile-X syndrome produced a range of 1·6% (Sutherland 1982) to 6·2% (Froster-Iskenius et al 1983).…”
Section: Introductionmentioning
confidence: 99%